039 The Birmingham joint motor disorder clinic: a descriptive study. Issue 10 (24th September 2010) - Savage, L; Tarrant, N; Rickards, H; Pall, H
Abstract : Aims: A joint motor disorder and psychiatry clinic is held at the Queen Elizabeth Hospital, Birmingham, once monthly. This descriptive study was designed to focus on three main areas: Referrals to the clinic: who is referred and for what reasons What happened in the clinic: diagnoses made and management options What happened after the clinic: patient follow-up Methods: Data were available for 260 clinic appointments, which, after removal of duplicate entries for patients who attended more than one appointment, resulted in a list of 123 patients. Medical notes were requested and, where unavailable, electronic clinical letters were sought. Two authors (LS and NT) collected data individually and, where clarification was required, both authors performed data collection and a consensus was reached. Data were entered onto Microsoft Excel for Mac 2008, and data analysis was performed using SPSS version 17 for Mac. Results: Of the 123 patients identified, 61% were male (mean age at referral 49.5 years). Neurologists referred over 50% of patients, and psychiatrists 27%. Approximately half of all patients referred had a previous psychiatric history; depression was most common. Parkinson's disease-related problems made up over a third of referrals (mainly psychosis and depression), and this group had a higher mean age at referral (62.5 years). Conditions related to Parkinson's disease accounted for 36% of diagnoses, and functional motor disorders 22%. The clinic made interventions (predominantly pharmacological at 53.6%) in approximately two-thirds of patients. Non-pharmacological therapies accounted for 10% of management decisions. A quarter of patients were discharged after one appointment, a third of whom were diagnosed with functional motor disorder. Sixteen per cent were discharged at a later date. The largest proportion of patients was still under follow up Conclusions: Two groups of patients were heavily represented in this clinic: patients with Parkinson's disease and those with functional motor disorders. The two populations differ in many aspects, from demographics to treatment and management. Overall, the clinic has a higher prevalence of previous psychiatric illness than one would expect in the general population. While this is understandable as the clinic is jointly run by a neuropsychiatrist, the patient's previous history of psychiatric illness did not necessarily directly relate to their reason for referral. Interventions were made in approximately two-thirds of cases, with pharmacological strategies being the most common. Treatment groups varied with respect to age, sex and diagnoses, that is patients with Parkinson's disease featured heavily in the pharmacological group, whereas patients with functional motor disorders were more represented in the non-pharmacological group.